Enterotoxigenic Escherichia coli Flagellin Inhibits TNF-Induced NF-κB Activation in Intestinal Epithelial Cells - Wang, Gaochan; Geisbrecht, Brian V.; Rueter, Christian; Hardwidge, Philip R. (My University, 2017)
Enterotoxigenic Escherichia coli (ETEC) causes childhood diarrhea in developing countries. ETEC strains produce the heat-labile enterotoxin (LT) and/or heat-stable enterotoxins (ST) and encode a diverse set of colonization factors used for adherence to intestinal epithelial cells. We previously found that ETEC secretes a heat-stable protein we designated as ETEC Secreted Factor (ESF) that inhibits the extent of NF-κB activation normally induced by tumor necrosis factor alpha (TNF). Here we fractionated ETEC supernatants using fast protein liquid chromatography (FPLC) and determined that ETEC flagellin was necessary and sufficient to protect IκBα from degradation in response to TNF stimulation. These data suggest a potentially novel mechanism by which ETEC may evade the host innate immune response by down-regulating NF-κB-dependent host responses.
Citation: Wang, G.; Geisbrecht, B.V.; Rueter, C.; Hardwidge, P.R. Enterotoxigenic Escherichia coli Flagellin Inhibits TNF-Induced NF-κB Activation in Intestinal Epithelial Cells. Pathogens 2017, 6, 18.